Sustainable Food Agricultural Land Preservation at Sleman Regency, Indonesia: An Attempt to Preserve Food Security - Widhiyastuti, Alfia Nisa; Adjie, Erra Melanie Ariesta; Fauzan, Adhia Azhar; Supriyadi, Supriyadi (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2023)
Urban development and increasing population impact improving the demand for non-agricultural land. Through the issuance of Law No. 41 of 2009 concerning the Protection of Sustainable Food Agricultural Land, the government has attempted to reduce the conversion rate of agricultural land by protecting paddy fields that are considered the potential for food supply. This study aims to examine the impact of the transformation of agricultural land to non-agricultural land on food security and the implementation of the of Law No. 41 of 2009. The research method used is survey and descriptive. The focus of discussion includes population growth, land change, land area, harvested area, production and food availability needs data. The data was gathered from field observations, interviews and a literature study. The results showed that the average decrease in paddy fields in the last three years was 98.87 ha. The population density in Sleman Regency is classified as high. In 2018 to 2019 the population density increased by 22.88 people km-2. In 2019 to 2020 the population density decreased by 163.35 people km-2. In 2018 to 2019 rice productivity increased by 625 tons ha-1, although harvested area and production have declined. There is no correlation between the location of paddy fields, population and rice productivity. The food security condition in Sleman Regency is generally stable, but the site of paddy fields that continues to decrease yearly must still be a concern.